A glossary for biometeorology - Gosling, Simon N.; Bryce, Erin K.; Dixon, P. Grady; Gabriel, Katharina M.A.; Gosling, Elaine. Y; Hanes, Jonathan M.; Hondula, David M.; Liang, Liang; Mac Lean, Priscilla Ayleen Bustos; Muthers, Stefan; Nascimento, Sheila Tavares; Petralli, Martina; et al. (2014)
Here we present, for the first time, a glossary of biometeorological terms. The glossary aims to address the need for a reliable source of biometeorological definitions, thereby facilitating communication and mutual understanding in this rapidly expanding field. A total of 171 terms are defined, with reference to 234 citations. It is anticipated that the glossary will be revisited in coming years, updating terms and adding new terms, as appropriate. The glossary is intended to provide a useful resource to the biometeorology community, and to this end, readers are encouraged to contact the lead author to suggest additional terms for inclusion in later versions of the glossary as a result of new and emerging developments in the field.